The Influence of Principal's Leadership on Teacher Performance in State Elementary Schools - Br. Perangin-angin, Almaria; Juliana; Wulan Sari HS, Dyan; Remigius Abi, Antonius; Sitepu, Anton; Janson Silaban, Patri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study discusses the influence of the principal's leadership on teacher performance in elementary schools. The research population of all teachers at public elementary school 047159 is 15. The sampling method used is non-probability sampling, specifically saturated sampling for 15 teachers. The data collection instrument is a questionnaire with a Likert scale that has 5 alternatives consisting of 110 items. The instrument validation test used the help of data processing results from SPSS version 25.0, while the instrument reliability used the Alpha Cronbach formula. Data analysis was conducted using simple regression analysis techniques. The research results indicate that the principal's leadership is high with a rate of 33% from the questionnaires filled out by the teachers, while performance is very high with a rate of 47%. Based on the research results, the principal's leadership influences the hypothesis test results, where the calculated value is 2.150 and the table value is 1.77. Thus, it influences the principal's leadership on the teachers' performance.